2018
DOI: 10.1007/s40123-018-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of Clinical and Economic Outcomes of Micro-Invasive Glaucoma Surgery (MIGS) in Primary Open-Angle Glaucoma

Abstract: IntroductionPrimary open-angle glaucoma is estimated to affect 3% of the population aged 40–80 years. Trabeculectomy is considered the gold standard in surgical management of glaucoma; however, it is a technically complex procedure that may result in a range of adverse outcomes. Device-augmented, minimally invasive procedures (micro-invasive glaucoma surgeries, MIGS) have been developed aiming for safer and less invasive intraocular pressure (IOP) reduction compared with traditional surgery.MethodsThis paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 74 publications
3
59
0
2
Order By: Relevance
“…MIGS procedures carry a superior safety profile compared with traditional surgery but are less effective at lowering IOP and reducing medication burden [47][48][49]. In addition, while MIGS offer a safer alternative to surgery for patients with mild-to-moderate disease who are intolerant to pharmacotherapy, such procedures still have attendant risks of adverse events such as infection and hypotony, often necessitating additional device-related interventions or surgery [50,51]. Studies also demonstrate that MIGS procedures are more effective in patients with higher baseline IOP.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…MIGS procedures carry a superior safety profile compared with traditional surgery but are less effective at lowering IOP and reducing medication burden [47][48][49]. In addition, while MIGS offer a safer alternative to surgery for patients with mild-to-moderate disease who are intolerant to pharmacotherapy, such procedures still have attendant risks of adverse events such as infection and hypotony, often necessitating additional device-related interventions or surgery [50,51]. Studies also demonstrate that MIGS procedures are more effective in patients with higher baseline IOP.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Recently, several new surgery implants, known as Minimally-Invasive Glaucoma Surgery (MIGS) have been developed to improve the efficacy and safety of conventional glaucoma surgery [5]. These implants work by increasing filtration of AH, either through its natural route (iStent implant), or by rerouting the AH flow into either the subconjunctival space (XEN implants and PreserFlo microshunt) or the suprachoroid space (CyPass Micro-Stent implant) [6].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that MIGS studies showed reduction of IOP, reduction of glaucoma medication, and a good safety profile, but much of these data came from comparative case studies, identifying a need for more RCTs of MIGS. Similarly, in the systemic review by Agrawal and Bradshaw, 5 nine RCTs were included and some MIGS procedures/devices were found to have no RCTs. They suggested that more "real world studies" and economic studies are needed to evaluate MIGS.…”
Section: Discussionmentioning
confidence: 99%